Separation and Determination of Phenobarbital and Guaifenesine in Commercial Pharmaceuticals Using Grafted Algerian Bentonite With SE-52 By Gas Chromatography - AZIZ RAMADAN, ABDUL; LAHMEK., M`HAMMED (Asian Journal of Chemistry, 2010)
Two pharmaceutical compounds i.e., phenobarbital and guaifenesine in several commercial pharmaceutical sources were investigated. These compounds were separated using grafted Algerian bentonite (B1100) with SE-52 as support. The compounds were determined by gas chromatography technique. The obtained analytical results show a good precision and reproducibility with a relative standard deviation of 2.8 and 2.9 % for phenobarbital and guaifenesine, respectively.